2013
DOI: 10.1002/grl.50157
|View full text |Cite
|
Sign up to set email alerts
|

Dipoles of the South East Madagascar Current

Abstract: [1] Satellite altimetry data covering 18 years together with hydrographic observations around south Madagascar show that after separation from the coast, the South East Madagascar Current (SEMC) propagates southwestward and breaks up into a regular series of symmetric counterrotating vortex pairs. Most of them split and propagate into the Agulhas retroflection system. Interannual variability of the dipole formation is related to the El Nino-Southern Oscillation. In the observation period two "early" Agulhas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 32 publications
7
54
0
2
Order By: Relevance
“…In contrast, a more recent investigation has shown that the SEMC flow dissolves into a series of cyclonic and anticyclonic dipole eddy pairs (Figure 1), and that there is no retroflection or westward jet [3]. Dipole pair formation occurs with a frequency of four to six per year, with most pairs breaking up shortly after formation and interacting with other mesoscale eddies [3]. However, recently it has been shown that the number of cyclonic eddies exceeds the anticyclonic eddies generated southwest of Madagascar [9].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In contrast, a more recent investigation has shown that the SEMC flow dissolves into a series of cyclonic and anticyclonic dipole eddy pairs (Figure 1), and that there is no retroflection or westward jet [3]. Dipole pair formation occurs with a frequency of four to six per year, with most pairs breaking up shortly after formation and interacting with other mesoscale eddies [3]. However, recently it has been shown that the number of cyclonic eddies exceeds the anticyclonic eddies generated southwest of Madagascar [9].…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies have suggested that the southern branch of the East Madagascar Current (SEMC) bifurcates, with a portion of the flow retroflecting and persisting east [4,5], and the remainder of the flow continuing west across the northern part of the Mozambique Basin (MB) and feeding into the Agulhas Current system (Figure 1), mainly in the form of mesoscale eddies [6][7][8][9][10]. In contrast, a more recent investigation has shown that the SEMC flow dissolves into a series of cyclonic and anticyclonic dipole eddy pairs (Figure 1), and that there is no retroflection or westward jet [3]. Dipole pair formation occurs with a frequency of four to six per year, with most pairs breaking up shortly after formation and interacting with other mesoscale eddies [3].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Downstream, the EMC seems to break up into a series of nearly symmetric dipolar vortex pairs off the southern tip of Madagascar. De Ruijter et al (2004) and Ridderinkhof et al (2013) suggest that the detachment of strong dipolar structures leads to events of early (easternmost) AC retroflection. Other suggestions have been presented in the literature on how the EMC contributes with source waters to the AC, such as by means of a retroflection regime characterized by castoff eddies and fragments feeding into the AC system (Lutjeharms et al 1981), through a minimized contribution due to a complete EMC retroflection (Lutjeharms 1988) or in the form of a direct southwestward flow to the upstream Agulhas region (Gründlingh 1993).…”
mentioning
confidence: 99%
“…Néanmoins, El Niño n'est pas obligatoirement responsable de la séche-resse car l'on observe qu'il n'y a pas de famines dans beaucoup de périodes de survenue d'El Niño. D'autres facteurs devraient être pris en compte, notamment, les phénomènes d'upwelling (Bemiasa, 2009et Voldsund, 2011 et l'Indian Ocean Dipole -IOD (Ridderinkhof et al, 2013). …”
Section: Ressources Halieutiques Potentielles Et Propositions D'adaptunclassified